Culture and Resilience At Work : a study of stress and hardiness among Indian corporate professionals - Mund, Pallabi, 1983- (New York, NY : Routledge, 2022)
"In 1979, Suzanne C. Kobasa propounded her theory of "hardiness" where she hypothesized her 3Cs: Commitment, Control, and Challenge, as the basic ingredients of hardiness that make an individual stress resilient. She was one of the early researchers who paid attention to personality features and illustrated that individuals who experience high level of stress without mental and physical illness have a different personality from those who become ill in stressful conditions. In current times, the discourse has enjoyed a sustained scholarly interest but there is hardly any study on the corporate professionals or the Indian context. Since the early 1990s, India has joined the corporate world and has been a fast-developing country. This changed state of affairs provides a broader scope of study on hardy personality in coping with stress in the Indian context. This book examines the efficacy of hardiness on the Indian corporate professionals in the post-globalization scenario. It endeavours to situate Kobasa's foundational theorisation along with those offered by other scholars in the context of the contemporary life situations with a focus on India. It presents a hypothesis that in the Indian context, culture could be looked upon as yet another basic component of hardiness. Culture and Resilience at Work offers an assessment of the significant contribution of Indian culture as one of the major contributing components in enhancing hardiness in corporate professionals. It will be of interest to researchers, academics, professionals, and students in the fields of stress management, human resource management, social psychology, culture studies, and organizational behaviour"--
Includes bibliographical references and index.
Keywords: Executives -- Job stress -- India; Corporate culture -- India; Resilience (Personality trait) -- India; Industrial psychiatry -- India